2015
DOI: 10.1542/peds.2014-2419
|View full text |Cite
|
Sign up to set email alerts
|

A School-Based Sleep Education Program for Adolescents: A Cluster Randomized Trial

Abstract: To evaluate the effectiveness of a multilevel and multimodal school-based education program.METHODS: A cluster randomized controlled trial with 14 secondary schools in Hong Kong and a total of 3713 students (intervention: 1545 vs control: 2168; 40.2% boys; mean age 6 SD: 14.72 6 1.53 years) were included in the final analysis. The intervention included a town hall seminar, small class workshops, a slogan competition, a brochure, and an educational Web site. Their parents and teachers were offered sleep educati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
77
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(82 citation statements)
references
References 45 publications
3
77
0
2
Order By: Relevance
“…We therefore cannot say that improvements in any of our outcomes were due to our program, as opposed to a re-testing or expectation effect. It will be particularly important for future work to include a control group since the control groups of some previous randomized controlled trials of sleep education programs have demonstrated improvements in sleep knowledge and quality (20;21;28). Also, tracking sleep with a sleep diary may itself constitute an intervention on its own, perhaps because monitoring leads to changes in the perception of a sleep complaint(58), or because patients obtain insight by linking sleep habits with sleep quality and quantity, particularly among individuals with insomnia (59).…”
Section: Discussionmentioning
confidence: 99%
“…We therefore cannot say that improvements in any of our outcomes were due to our program, as opposed to a re-testing or expectation effect. It will be particularly important for future work to include a control group since the control groups of some previous randomized controlled trials of sleep education programs have demonstrated improvements in sleep knowledge and quality (20;21;28). Also, tracking sleep with a sleep diary may itself constitute an intervention on its own, perhaps because monitoring leads to changes in the perception of a sleep complaint(58), or because patients obtain insight by linking sleep habits with sleep quality and quantity, particularly among individuals with insomnia (59).…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion criteria for iRBD probands included (1) diagnosis of video‐polysomnography (vPSG)‐confirmed iRBD, (2) onset of RBD symptoms in the absence of any preceding neurodegenerative disease, and (3) absence of comorbid narcolepsy. Non‐RBD control probands were recruited from the community (80% were recruited from the family members of a community‐based study in our Sleep Education Program) and our sleep clinic (20%). To minimize potential referral bias, recruitment of the majority of probands was intentionally community based.…”
Section: Methodsmentioning
confidence: 99%
“…[17][18][19] However, the magnitude of the effect size found in the current study was larger than those reported in RCTs of school-based sleep education programs. 70,71 This might be due to several factors. The Sleep SENSE interventions were personally tailored, more intensive, had a key focus on engagement and reviewing key information to increase retention and recall, and provided adequate opportunities to practice techniques in session and at home.…”
Section: Hypotheses One and Two-treatment Effectsmentioning
confidence: 99%